HLA micropolymorphisms strongly affect peptide-MHC multimer-based monitoring of antigen-specific CD8+ T cell responses - van Buuren, Marit M; Dijkgraaf, Feline E; Linnemann, Carsten; Toebes, Mireille; Chang, Cynthia X L; Mok, Juk Yee; Nguyen, Melanie; van Esch, Wim J E; Kvistborg, Pia; Grotenbreg, Gijsbert M; Schumacher, Ton N M (The Journal of immunology (1950), 2014)
Peptide-MHC (pMHC) multimers have become one of the most widely used tools to measure Ag-specific T cell responses in humans. With the aim of understanding the requirements for pMHC-based personalized immunomonitoring, in which individuals expressing subtypes of the commonly studied HLA alleles are encountered, we assessed how the ability to detect Ag-specific T cells for a given peptide is affected by micropolymorphic differences between HLA subtypes. First, analysis of a set of 10 HLA-A*02:01-restricted T cell clones demonstrated that staining with pMHC multimers of seven distinct subtypes of the HLA-A*02 allele group was highly variable and not predicted by sequence homology. Second, to analyze the effect of minor sequence variation in a clinical setting, we screened tumor-infiltrating lymphocytes of an HLA-A*02:06 melanoma patient with either subtype-matched or HLA-A*02:01 multimers loaded with 145 different melanoma-associated Ags. This revealed that of the four HLA-A*02:06-restricted melanoma-associated T cell responses observed in this patient, two responses were underestimated and one was overlooked when using subtype-mismatched pMHC multimer collections. To our knowledge, these data provide the first demonstration of the strong effect of minor sequence variation on pMHC-based personalized immunomonitoring, and they provide tools to prevent this issue for common variants within the HLA-A*02 allele group.